2019
DOI: 10.3389/fchem.2019.00735
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rice Husk and Wood Biomass Properties on the Manufacture of Filaments for Fused Deposition Modeling

Abstract: Additive manufacturing or 3D printing has the potential to displace some of the current manufacturing techniques and is particularly attractive if local renewable waste resources can be used. In this study, rice husk, and wood powders were compounded in polylactic acid (PLA) by twin screw extrusion to produce filaments for fused-deposition modeling 3D printing. The biomasses were characterized in terms of physical features (e.g., particle size, density) and chemical compositions (e.g., solid state nuclear magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 41 publications
2
45
0
Order By: Relevance
“…The studies [ 19 , 31 , 32 , 33 , 43 , 45 , 46 , 48 , 53 , 57 , 58 , 60 , 61 ] were missing either one or both of information (fiber wt% or maximum tensile strength) and these studies [ 56 , 59 , 65 , 67 , 73 ] did not include tensile strength as a part of their evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies [ 19 , 31 , 32 , 33 , 43 , 45 , 46 , 48 , 53 , 57 , 58 , 60 , 61 ] were missing either one or both of information (fiber wt% or maximum tensile strength) and these studies [ 56 , 59 , 65 , 67 , 73 ] did not include tensile strength as a part of their evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the flexural properties deteriorated with increasing fiber length, which produced large pores in the infill interlayer and led to adhesion failure in printed specimens. The experiments by Guen et al [ 46 ] revealed that the mechanical properties were reduced by the addition of wood and rice husk fillers to the polymer due to the weakening of the inter-strand cohesion in the printed objects. Daver et al [ 48 ] found that the tensile mechanical properties of the composites deteriorated as the cork content increased while the impact strength initially decreased with the introduction of cork but then increased as the cork content became higher.…”
Section: Printing Failures and Issuesmentioning
confidence: 99%
“… These dataset may also open new perspectives for wider uses of biomass in innovative applications, for which advanced granulometric reduction is required (e.g. 3D-printing, smart materials, solid biofuels…) [11] , [12] , [13] . …”
Section: Value Of the Datamentioning
confidence: 99%
“…Recently, agricultural residues have been used as a loading material for 3D printing [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ] as they reduce warping [ 54 , 55 , 56 , 57 ], enhance printing directionality [ 58 , 59 , 60 ], and display high specific mechanical properties [ 61 , 62 , 63 ]. However, in FFF there are some standing issues such as residues’ agglomeration, viscosity variations, high porosity, low thermal stability [ 64 ], and non-uniform physical and mechanical properties [ 61 ].…”
Section: Introductionmentioning
confidence: 99%